2014
DOI: 10.1007/s12105-014-0567-z
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Sarcomatous Transformation of Fibrous Dysplasia

Abstract: A case of osteosarcoma developing from fibrous dysplasia of the sphenoid bone in a 59-year-old female will be discussed. The characteristic radiologic and histologic features of the entity will be described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…Hence, interpretation of genetic alterations must always be performed in the context of morphology and imaging. 26,27 Our findings support prior observations that in the appropriate context, the detection of a GNAS mutation in a primary bone tumor is supportive of a diagnosis of fibrous dysplasia, and GNAS mutations rarely, if ever, occur in parosteal osteosarcoma. The reason for the findings by Carter and colleagues, however, remain elusive.…”
Section: Discussionsupporting
confidence: 87%
“…Hence, interpretation of genetic alterations must always be performed in the context of morphology and imaging. 26,27 Our findings support prior observations that in the appropriate context, the detection of a GNAS mutation in a primary bone tumor is supportive of a diagnosis of fibrous dysplasia, and GNAS mutations rarely, if ever, occur in parosteal osteosarcoma. The reason for the findings by Carter and colleagues, however, remain elusive.…”
Section: Discussionsupporting
confidence: 87%
“…A malignant transformation of FD is rare, which occurs less than 1% of cases [19, 20]. In present study, the clinicians performed biopsy or surgery for 13 of the patients.…”
Section: Discussionmentioning
confidence: 92%
“…After applying the inclusion and exclusion criteria, 14 studies were included for review. The manual search added five more studies, resulting in 19 articles included in this systematic review reporting the malignant transformation of 27 patients with FOLs . Only cases that fulfilled all the inclusion criteria within case series studies were included in this review.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the outcome, five studies did not report any follow‐up information and one study only reported that the patient did not respond to therapy, yet the time of follow‐up was not mentioned . Among the other reports (n = 21), eight patients remained alive during the follow‐up, while 13 died because of the tumor.…”
Section: Resultsmentioning
confidence: 99%